The Effect of Income Polarization on Crime: Evidence From Court Judicial Documents in China - Jingqi Liu; Chen Wang; Yuzhou Wang (International Studies of Economics)
ABSTRACT Crime affects social stability and people's safety, and directly increases the cost of urban development. Existing literature shows that income distribution affects crime, but it mainly focuses on the effect of income inequality and poverty, with scant evidence addressing the impact of income polarization on crime. Applying data from the China Household Finance Survey (CHFS) and judicial documents from 2014 to 2018, this paper demonstrates that rising income polarization significantly increases crime in cities. The result still holds after a series of robustness checks. Heterogeneity analyses show that income polarization has a more pronounced effect on criminal activities related to violence, robbery and stealing, drug and financial fraud. Moreover, cities with a higher proportion of young and migrant populations would be more adversely affected by income polarization. Mechanism analyses indicate that income polarization exacerbates crime by increasing alienation, reducing job‐seeking willingness and happiness of residents.